The loss of left atrial contractile function predicts worse outcome in HFrEF: a speckle tracking study. (8th February 2021) - Mandoli, GE; Pastore, MC; Benfari, G; Setti, M; Maritan, L; D"ascenzi, F; Focardi, M; Carrucola, C; Vigna, M; Valente, S; Mondillo, S; Cameli, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: in chronic heart failure (HF), high cardiac pressure induces a progressive remodeling of small pulmonary arteries up to pulmonary hypertension development. At the end of left atrial (LA) conduit function, pulmonary and left heart end-systolic pressures equalize. This might affect LA systole. Purpose: we investigated whether peak atrial contraction strain (PACS), measured by speckle tracking echocardiography (STE), was independently associated with outcome in HF with reduced ejection fraction(HFrEF). Methods: 168 outpatients with HFrEF and sinus-rhythm referred to our echo-labs were prospectively enrolled. After clinical and echocardiographic evaluation, off-line STE analysis was performed. The endpoints were cardiovascular (CV) death and HF hospitalization respectively. Spline knotted survival model identified the optimal cut-off value for PACS. Results: The 152 included patients were stratified based on PACS < 8%(n = 76) or PACS≥8%(n = 76). Mean age was 61 ± 12, mean EF was 30 ± 9%. Characteristics of the two groups are presented in Table 1. Over a mean follow-up of 3.41 ± 1.9 years, 117 events (51 CV death, 66 HF hospitalizations) were collected. By univariate and multivariate Cox analysis, global PACS emerged as a strong and independent predictor of CV death and HF hospitalization, even after adjusting for age, sex, LV strain, E/e', LA volume index (HR 0.6 per 5 unit decrease in PACS). Kaplan Meier curves showed a sustained divergence in event-free survival rates for the two groups (Fig.1). Conclusions: The reduction of PACS significantly and independently affects CV outcome in HFrEF. Although limited to patients with sinus rhythm, it could offer additive prognostic information for HFrEF patients.